Peranan Taman Bacaan Masyarakat Pelangi Ilmu dalam Pemberdayaan Masyarakat di Desa Pematang Seleng: The Role of the Pelangi Ilmu Community Reading Park in Community Empowerment in Pematang Seleng Village - Tuzzahrah, Fadilla; Franindya Purwaningtyas (Information Technology and Science(ITScience), 2025)
This study aims to analyze the role of TBM Pelangi Ilmu in community empowerment in Pematang Seleng village. The focus of this study is to identify the role, programs, and impacts in improving community empowerment in Pematang Seleng village. This study uses a descriptive qualitative method to understand community phenomena and their relationship with the research subjects. Data collection techniques in this study were carried out through in-depth interviews with the founder and manager of TBM Pelangi Ilmu regarding the role, programs, and impacts in improving community empowerment, as well as documentation. The results of the study indicate that there are several roles in community empowerment, and there are superior programs. The superior programs carried out by TBM Pelangi Ilmu are